Kemampuan Melakukan Pengukuran Antropometri Pada Kader Posyandu Sebelum Dan Sesudah Dilakukan Pendampingan Intensif Di Desa Tambakrejo, Gresik - Alfania, Dinda Eka; Rahma, Amalia; Ariestiningsih, Eka Srirahayu (Universitas Muhammadiyah Gresik, 2023)
Posyandu represents a fundamental healthcare initiative established and supported by community health personnel. This research goal to see level of knowledge and skills of posyandu cadres before and after intensivementoring. The research method was quantitative with a quasi-experimental research design with a pretest-postest design without control group design, with 35 samples with total sampling techniques using measuring instruments used on posyandu cadre knowledge variables using posyandu cadre knowledge questionnaires on anthropometric measurements and ability variables using checklist sheets measuring cadre skills in making anthropometric measurements.The results of this research posyandu cadres knowledge and skills p value knowledge data of 0.000 ≤ α 0.05 was obtained and data on the amiability of cadres p value 0.000 ≤ α 0.05 which means that there are differences in the level of knowledge and skills of cadres before and after intensive assistance was carried out. Increasing knowledge can be done by mentoring through counseling using educational media. Skill improvement can be done after counseling by conducting training for posyandu cadres. Keywords: Knowledge, Posyandu Cadres, Skills, Stunting